2022
DOI: 10.1002/pon.5910
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the family communication environment on burden and clinical communication in blood cancer caregiving

Abstract: Objective: We examined the effects of the family communication environment (conversation orientation) on adult child caregivers' burden and clinical interactions and if the effects are mediated by openness to communicate about cancer, avoidant cancer communication, and social support (SS).Method: Caregivers of a parent diagnosed with a blood cancer (N = 121) completed an online survey of validated measures of conversation orientation (i.e., the extent to which families openly communicate), SS, cancer openness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Ongoing care burden and distress can inhibit caregivers’ sense of control and ability to cope or engage in caregiving [ 33 ] and is also associated with less openness between caregivers and their diagnosed loved one [ 34 ]—effects that are all detrimental to disease management. CLL caregivers in the survey study indicated they need ongoing, reliable information from experts on COVID-19 risk that is specifically targeted to CLL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing care burden and distress can inhibit caregivers’ sense of control and ability to cope or engage in caregiving [ 33 ] and is also associated with less openness between caregivers and their diagnosed loved one [ 34 ]—effects that are all detrimental to disease management. CLL caregivers in the survey study indicated they need ongoing, reliable information from experts on COVID-19 risk that is specifically targeted to CLL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other interventions focus primarily on concepts and tasks such as mindfulness [ 38 , 39 ]; stress management [ 40 ]; patient symptom management [ 40 ]; and topics such as goal setting, planning, accessing family support services, and building problem-solving skills [ 41 ]. Our previous research has shown that adult child caregivers’ families who communicate more openly report less caregiver burden, better clinical interaction skills, and better perceived quality of the clinical interaction [ 17 ]. Interventions that help family caregivers hone their communication skills are a critical component to supporting caregivers as they navigate the difficulties of caring for a loved one with a blood cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The Healthy Communication Practice is a self-paced, web-based program developed for adult children who care for a parent, parent-in-law, or stepparent currently living with a blood cancer (eg, leukemia, lymphoma, myeloma). Grounded in communication and education theories [ 18 - 25 ] and based on our extensive preliminary work (in-depth interviews and surveys) with cancer caregivers [ 14 - 17 ], this program teaches caregivers essential communication skills in eHealth literacy, clinical encounters, and family relationships. We teach concepts and skills to help caregivers navigate web-based cancer information, communicate with their parent’s doctors, find meaning in their caregiver role, and use open and supportive communication to strengthen relationships and facilitate communication within their family.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of open communication in parent-child bonds after a cancer diagnosis may even extend to better clinical communication. For instance, when midlife adult child caregivers report more open communication with their parent diagnosed with a blood cancer, they also report better clinical communication experiences with their parent's clinicians [60]. While open communication may promote better biopsychosocial outcomes and disease adjustment both at home and in the clinic, studies informing the Family Communication Patterns Theory (FCP) have demonstrated that family relationships develop patterns or norms of communicating over their relational history that are characterized, in part, by how openly (or not) they communicate [61].…”
Section: Mother-daughter Communication and Breast Cancer Coping And C...mentioning
confidence: 99%